Impact of â€œGreen Fuel Promotionâ€ on Customer Buying Behavior in Indian Retail Fuel Outlets : A Mix-Method Approach Using fsQCA and NVIVO - Routray, Manash; Giri, Arunangshu (Indian Journal of Marketing, 2024)
Purpose : Oil companies in India have been increasingly investing in green fuel initiatives, including biofuels and renewable energy sources. These efforts aimed to reduce carbon emissions and supported the country’s shift toward a sustainable energy future. This study investigated the effect of green fuel promotions in Indian retail fuel outlets on customer purchasing behaviour. Methodology : Six independent latent variables (namely brand image, awareness, loyalty program, technological progression, social engagement, and cultural values) that impacted purchase decisions were undertaken in the study. A mixed-method approach, combining both qualitative and quantitative techniques, was employed in this research, using NVIVO-14 and fsQCA 3.0 software. Findings : This short communication explored psychological, social, and cultural aspects of green promotion that are driving impetus toward customer buying behaviour in Indian retail fuel outlets. We found that customer awareness and loyalty programs under ‘Psychological Factor’ had a noteworthy impact on customers’ green-fuel purchase decisions. Practical Implications : It was recommended that oil companies must invest in consumer education initiatives to enhance awareness and implement effective loyalty programs. This study will also help oil companies to understand different important facets of green fuel promotion, which will facilitate to increase in customer satisfaction and survival in a competitive market. Originality : Unlike prior research on green promotion, this research built a model to examine consumer buying behaviour impacted by green fuel promotion in Indian retail fuel outlets. In this study, this model was developed using the consumer behavior model.